"Should WE Stand Together?": A systematic review and meta‐analysis of the effectiveness of family‐based interventions for adults with chronic physical diseases. Issue 4 (12th August 2021) - Sousa, Helena; Ribeiro, Oscar; Afreixo, Vera; Costa, Elísio; Paúl, Constança; Ribeiro, Fernando; Figueiredo, Daniela
Abstract: Family support has been identified as an important factor for the psychological adjustment of patients with chronic physical conditions. This study aimed to systematically review and conduct a meta‐analysis of studies comparing the effectiveness of family‐based versus patient‐oriented interventions for chronic physical conditions. The search was performed between April 12 and April 29, 2021, on Web of Science (all databases included), Scopus, PsycINFO, and CENTRAL. Thirteen RCTs were included. The results favored family‐based interventions for various patient outcomes related to pain, distress, self‐efficacy, social and emotional function, coping, the welfare of the domestic environment, capacity to mobilize social support, and sexual relationships with medium to large effect sizes (Cohen's d range: 0.45–0.90). This type of intervention also decreased family members' anxiety, depression, sleep problems, and distress, improving search and presence of meaning in life, social support, the support provided to the patient, and sexual relationships with medium to very large effect sizes (Cohen's d range: 0.58–2.76). The meta‐analytical findings suggested that the patients' ( k = 12, d = 0.34; 95% CI = 0.13–0.55, I 2 = 74%, p < 0.01) and family members' ( k = 4, d = 0.68; 95% CI = 0.08–1.27, I 2 = 88%, p < 0.01) psychosocial outcomes significantly improved with family‐based interventions compared with patient‐oriented interventions. The meta‐analysis of patients' self‐efficacy showed a medium‐size effect ( d = 0.64; k = 3; I 2 = 19%). The results suggest a trend toward the beneficial effects of family‐based interventions, but more research is needed with higher quality RCTs to confirm this hypothesis. Resumen: El apoyo familiar se ha reconocido como un factor importante para la adaptación psicológica de los pacientes con enfermedades físicas crónicas. El presente estudio tuvo como finalidad analizar sistemáticamente y realizar un metaanálisis de estudios que comparan la eficacia de las intervenciones familiares y de las orientadas al paciente en las enfermedades físicas crónicas. La búsqueda se realizó entre el 12 de abril y el 29 de abril de 2021 en Web of Science (se incluyeron todas las bases de datos), Scopus, PsycInfo, y CENTRAL. Se incorporaron trece ensayos clínicos aleatorizados y controlados. Los resultados favorecieron las intervenciones familiares en los casos de diferentes desenlaces de los pacientes relacionados con el dolor, el distrés, la autoeficacia, la función social y emocional, el afrontamiento, el bienestar del entorno doméstico, la capacidad de movilizar el apoyo social, y las relaciones sexuales con tamaños del efecto entre medianos y grandes (rango de la d de Cohen: entre 0.45 y 0.90). Este tipo de intervención también disminuyó la ansiedad, la depresión, los problemas de sueño y el distrés de los miembros de la familia, mejoró la búsqueda y la presencia del significado en la vida, el apoyo social, el apoyo brindado al paciente y las relaciones sexuales con tamaños del efecto entre medianos y muy grandes (rango de la d de Cohen: entre 0.58 y 2.76). Los resultados metaanalíticos sugirieron que los resultados psicosociales de los pacientes (k = 12, d = 0.34; 95 % CI = 0.13―0.55, I2 = 74 %, p<.01) y de los familiares (k = 4, d = 0.68; 95 % CI = 0.08―1.27, I2=88 %, p<.01) mejoraron considerablemente con las intervenciones familiares en comparación con las intervenciones orientadas a los pacientes. El metaanálisis de la autoeficacia de los pacientes demostró un efecto de tamaño mediano (d = 0.64; k = 3; I2 = 19 %). Los resultados sugieren una tendencia hacia los efectos beneficiosos de las intervenciones familiares, pero se necesitan más investigaciones con ensayos controlados aleatorizados de mayor calidad para confirmar esta hipótesis. 摘要: 家庭支持被认为是慢性身体疾病患者心理调整的一个重要因素。本研究旨在系统地回顾并进行meta分析，比较以家庭为基础和以患者为导向的干预对慢性身体疾病的有效性。该研究于2021年4月12日至4月29日期间针对Web of Science(包括所有数据库)、Scopus、PsycInfo和CENTRAL上的研究进行荟萃分析，包括了13项随机对照试验。研究结果支持以家庭为基础的干预措施，对患者的各种结果进行干预，这些结果涉及疼痛、痛苦、自我效能感、社会和情绪功能、应对、家庭环境的福利、动员社会支持的能力以及中到大的效应量(Cohen's d范围: 0.45 ‐ 0.90)。这种类型的干预也减少了家庭成员的焦虑、抑郁、睡眠问题和痛苦，改善了对生活意义的寻找和存在、社会支持、提供给患者的支持以及中等到非常大的效应量的性关系(Cohen's d范围:0.58到2.76)。荟萃分析结果显示，基于家庭的干预明显改善了患者（k = 12，d = 0.34；95% CI = 0.13‐0.55，I2 = 74%，p<.01）和家庭成员（k = 4，d = 0.68；95% CI = 0.08‐1.27，I2 = 88%，p<.01）的社会心理结果。对患者自我效能的荟萃分析显示出中等规模的影响（d=0.64；k=3；I2=19%）。结果表明，基于家庭的干预趋向于有益的效果，但需要更多的研究和更高质量的RCT来证实这一假设。